(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Osteoarthritis (OA) is a common joint disorder. Oal non-steroidal anti- inflammatory drugs (NSAIDs), including selective cyclooxygenase-2 (COX-2) inhibitors, are the mainstay of pharmacotherapy but it can not be used for long time due to their adverse effects. Diacerein is SYSADOAs, an advantage of using diacerein in OA treatment is, that Diacerein does not affect the synthesis of prostaglandins, and does thereby not have a deleterious effect on the upper gastro-intestinal mucosa. This is an important advantage compared to NSAID treatment. But still there is still no consensus on the place of Diacerein in OA because there is lack of pragmatic trials those have evaluated the effectiveness of Diacerein in real life situations.Objective: So this study was planned to evaluate the effectiveness of Diacerein in symptomatic treatment of knee OA.Methods: All the Patients were given Diacerein 50 mg BD. The evaluation of effectiveness will be in terms of improvements in symptoms and physical functions of patients.Results: Diacerein is not as effective in controlling clinical symptoms of knee Osteoarthritis as it claimed to be. It also takes long time to show a clinically relevant & appreciable effect. Conclusion: Diacerein is a overrated drug in Osteoarthritis which is mainly due to lack of pragmatic trials of this drug. Pragmatic clinical trials should must be done to know the real place of a drug in management of any condition